2018
DOI: 10.1016/j.ajme.2018.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study between multi-detector computed tomography and echocardiography in evaluation of congenital vascular rings

Abstract: Vascular rings are unusual anomalies represent less than 1% of all cardiac anomalies, it is abnormal development of aortic arch complex leading to formation of a ring formed by vessels that encircle both the trachea and esophagus, echocardiography had limited acoustic window which leads to inadequate evaluation of great vessels, Multi-detector computed tomography (MDCT) is one of the most important non invasive diagnostic tool for detection the vascular ring anomalies. The Aim: To evaluate role of MDCT Scannin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
1
0
0
Order By: Relevance
“…As regards vascular rings detected, Echo and MDCT had 50% and 100% sensitivity respectively for detection of vascular rings when compared to conventional angiography. The detected types of vascular rings were double aortic arch with right arch predominance and right side aortic arch with aberrant left subclavian which was consistent with Hamisa et al [12] who concluded that double aortic arch and right side aortic arch with aberrant left subclavian were the commonest forms of vascular rings in their study with 100% sensitivity for MDCT in vascular rings detection.…”
Section: Discussionsupporting
confidence: 88%
“…As regards vascular rings detected, Echo and MDCT had 50% and 100% sensitivity respectively for detection of vascular rings when compared to conventional angiography. The detected types of vascular rings were double aortic arch with right arch predominance and right side aortic arch with aberrant left subclavian which was consistent with Hamisa et al [12] who concluded that double aortic arch and right side aortic arch with aberrant left subclavian were the commonest forms of vascular rings in their study with 100% sensitivity for MDCT in vascular rings detection.…”
Section: Discussionsupporting
confidence: 88%